Acquired pellicle engineering for the control of erosive tooth wear: in vitro and in situ evaluation of the protective potential of a sugarcane-derived cystatin (CaneCPI-5) - Gironda, Carlos Condarco (2023)
Erosive tooth wear (ETW) is a complex and multifactorial problem that requires special attention for prevention and treatment. Saliva is an essential biological factor that plays a crucial role in protecting against ETW. A large part of saliva\'s role comes from the fact that its proteins are the major constituents of the acquired pellicle, since some proteins in this integument are resistant to removal due to erosive challenges, and are therefore candidates for incorporation into dental products aimed at preventing ETW. In the present work, the protective effect of a sugarcane-derived cystatin, added to different solutions and gels, was evaluated in vitro and in situ. In the first chapter, an in vitro study was performed to evaluate the protective effect of gels containing different concentrations of CaneCPI-5 against initial enamel erosion (challenge with 0.65% citric acid, pH 3.4, for 1 min). Results indicated that treatment with gels containing CaneCPI-5 at concentrations of 0.1 or 1.0 mg/mL protected enamel against initial erosion, probably because CaneCPI-5 increases the number of electron donor sites on the surface, which can impact the formation of the acquired pellicle. In the second chapter, different vehicles containing CaneCPI-5 were evaluated in situ, using a crossover and double-blind protocol, conducted for 5 days in each phase. The volunteers used an apparatus containing 4 specimens of human dentin for 5 days. Specimens were treated with 1 drop of the tested solutions for 60 s before being submitted to erosive challenges (0.1% citric acid, pH 2.5, 90 s, 4X/day), combined or not with abrasive challenges (brushing for 15 s, 2X/day). The treatment with the gels was performed only once/day. In the first part, the solution containing 0.1 mg/mL CaneCPI-5 was tested against a positive control (Elmex Erosion Protection) and a negative control (deionized water). Both treatments significantly reduced dentin loss compared to the negative control for both erosion and erosion associated with abrasion. In the second part, the evaluated groups were: no treatment, chitosan gel, chitosan gel containing 12300 ppm F and chitosan gel containing CaneCPI-5 0.1 mg/mL. The lowest wear was observed for the gel containing CaneCPI-5, which despite not differing from the NaF gel, was the only gel that differed from the chitosan gel. This is the first in situ study in which the effect of CaneCPI-5 to reduce dentin erosive wear was evaluated, since previous studies only analyzed enamel. Our data reinforce the findings indicating that the addition of CaneCPI-5 to both solutions and gels seems to be a promising alternative to reduce ETW through acquired pellicle engineering. Clinical application protocols should be tested, combining professional application of the gel with home application of the solution containing CaneCPI-5.